THE ROLE OF COGNITIVE FRAMES IN SHAPING NARRATIVE STRUCTURES: A STYLISTIC ANALYSIS OF CONTEMPORARY ENGLISH FICTION - Husanova Dilshoda Abduganiyevna (TADQIQOTLAR.UZ, 2024)
Annotation: Stylistic processes in literature play a crucial role in shaping the aesthetic, emotional, and intellectual impact of literary texts. This article explores the significance  of  stylistic  processes  from  a  cognitive  perspective,  examining  how language choices, narrative techniques, and linguistic devices contribute to the reader's understanding and interpretation of literary works. By employing cognitive theories of language and perception, we delve into the intricate ways in which stylistic elements engage  readers'  mental  faculties,  evoke  imagery,  and  elicit  emotional  responses. Through  examples  drawn  from  various  literary  genres  and  periods,  this  article illustrates the diverse manifestations of stylistic processes and their profound influence on literary meaning and reception.